2021
DOI: 10.3390/molecules26092666
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin for the Food Industry

Abstract: Xanthophyll astaxanthin, which is commonly used in aquaculture, is one of the most expensive and important industrial pigments. It is responsible for the pink and red color of salmonid meat and shrimp. Due to having the strongest anti-oxidative properties among carotenoids and other health benefits, natural astaxanthin is used in nutraceuticals and cosmetics, and in some countries, occasionally, to fortify foods and beverages. Its use in food technology is limited due to the unknown effects of long-term consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
120
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 99 publications
0
120
0
2
Order By: Relevance
“…AX is a carotenoid that is frequently found in aquatic organisms, where it contributes its bright orange-to-red color, as in the shells of shrimp and crab, and in the muscles of salmon and trout [ 7 , 8 , 9 ]. Although AX is best recognized as a pigment characteristic of aquatic organisms, it’s extensive presence in prokaryotes and eukaryotes is less commonly known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AX is a carotenoid that is frequently found in aquatic organisms, where it contributes its bright orange-to-red color, as in the shells of shrimp and crab, and in the muscles of salmon and trout [ 7 , 8 , 9 ]. Although AX is best recognized as a pigment characteristic of aquatic organisms, it’s extensive presence in prokaryotes and eukaryotes is less commonly known.…”
Section: Introductionmentioning
confidence: 99%
“…The hydroxyl groups of AX can bind to fatty acids, sugars, or proteins. In addition, the central polyene chain often has an all-trans configuration, but there are also geometric isomers, in which portion(s) of AX may bear a cis configuration [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cost of producing synthetic astaxanthin is around 880 €•kg −1 ; therefore, natural astaxanthin cannot compete in terms of cost (for food applications). However, synthetic astaxanthin cannot be used as food in the EU and in the US, and, therefore, natural astaxanthin produced in the EU and the US is the only permitted ingredient for food and the preferred option for high-end applications [12]. Conversely, in China, a recent study predicted the production cost of natural astaxanthin to be as low as 610 €•kg −1 , which is encouraging as this value would allow the microalgal process to compete with the synthetic alternative [13].…”
Section: Introductionmentioning
confidence: 99%
“…AST was first isolated from lobster by Kuhn and Sorensen in 1938 [2]. The AST is 3,3 -dihydroxy-β,β-carotene-4,4 -dione (Figure 1), and its molecular formula is C 40 H 52 0 4 [3]. It was demonstrated that AST is produced by some microorganisms, including bacteria (e.g., Escherichia coli, Mycobacterium lacticola, Paracoccus carotinifaciens, and Brevibacterium sp.…”
Section: Introductionmentioning
confidence: 99%